Evaluation of the Competency and Skills Needs for Seaplane Maintenance in Pilot Education at the Indonesian Pilot Academy Banyuwangi - Prayitno, Hadi; Sunardi; Mubarok, Ahmad; Setyo, Demmy; Hariadi, Setyo (JTP - Jurnal Teknologi Pendidikan, 2024)
This research assesses the competency and skill requirements for Seaplane aircraft maintenance in the pilot education program at the Indonesian Pilot Academy Banyuwangi. Utilizing qualitative methods, including in-depth interviews and direct observation, the study involves students and teachers in the pilot education program. Analysis reveals crucial competencies for students, encompassing a profound understanding of Seaplane aircraft systems, adept problem-solving during operations, and the capacity for quick and precise decision-making. Special skills, such as adaptability to complex working conditions and meticulousness in maintenance procedures, are also deemed essential. The research identifies alignment between the academy's curriculum and Seaplane aircraft maintenance needs, yet highlights specific areas requiring enhancement. The study recommends strengthening the curriculum and teaching methods to better address competency and skill needs. Implementing these recommendations is anticipated to elevate the quality of graduates, ensuring they are well-equipped to meet the challenges of Seaplane aircraft maintenance in the aviation industry.